Input Data Acquisition Possibilities for Numerical Simulation of Drawing Process by means of the Contact-less Optical System and Thermo-camera - Sobotka, Jiri; Solfronk, Pavel; Kolnerova, Michaela; Korecek, David (Manufacturing Technology Journal, 2019)
Drawing process is generally influenced by many technological parameters (e.g. holding pressure, friction coefficient, etc.) and all of them should be considered for numerical simulation of such process. This paper deals with the possibilities how to determine one of the parameters that is quite difficult to be taken into account - magnitude of heat generated during forming process. In this case only heat generated by plastic deformation was determined, thus static tensile test at different loading rates was performed. Contact-less optical system ARAMIS and Thermo-camera FLIR SC660 was used to measure distribution of both plastic deformation and temperature on samples surfaces.
Keywords: Contact-less Measurement; Thermo-camera; Static Tensile Test; Formability; Numerical Simulation